Study of gate leakage mechanism in advanced charge-coupled MOSFET (CC-MOSFET) technology. (February 2016) - Barletta, G.; Ngwan, V.C.
Abstract: In this work we present an alternative method to evaluate the ability to charge trap of the thermal silicon oxide grown on n + -polysilicon in charge-coupled MOSFET devices. By interpreting the current conduction mechanism through the polysilicon-oxide by Frenkel–Poole model, we were able to evaluate and quantify the amount of charge trapped in it. We propose this approach as a very simple methodology to recognize the properties and quality of insulation of the thermal silicon oxide grown on n + -polysilicon devices.